PENGARUH LIKUIDITAS, LEVERAGE, DAN KOMITE AUDIT TERHADAP AGRESIVITAS PAJAK - Agus Alifia Putri; Rheny Afriana Hanif (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
The aim of this study was to analyze the effect of liquidity, leverage, and audit committee on tax aggressiveness. Effective tax rate (ETR) used to measure tax aggressiveness. Population on this study is a manufacturing companies listed on the Indonesia Stock Exchange period 2016-2018. 74 companies were selected using the purposive sampling method. This study uses documentation data collection methods obtained from data tracking through electronic media such as annual report data and company financial statements that are sampled. Data processing techniques in this study use the method of multiple linear regression analysis with SPSS Version 25. The results of this study indicate that the liquidity and audit committee have negative effect on tax aggressiveness While leverage has a positive effect on tax aggressiveness